Answer:
-17/12
Step-by-step explanation:
-(2/3)-(3/4)
-(8/12)-(9/12)
-17/12
The correct answer is a.y=3x-4
4(x - 8) = (2)(5)
4x - 32 = 10
4x = 42
x = 10.5
Answer:
C. ![a_n=(9)(\frac{2}{3})^{n-1}](https://tex.z-dn.net/?f=a_n%3D%289%29%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7Bn-1%7D)
Step-by-step explanation:
Iterative geometric sequence:
![a_n=a_1x^{n-1}](https://tex.z-dn.net/?f=a_n%3Da_1x%5E%7Bn-1%7D)
Recursive geometric sequence:
![a_n=xa_{n-1}](https://tex.z-dn.net/?f=a_n%3Dxa_%7Bn-1%7D)
The equations are very similar and you only really need to rearrange it. The factor (2/3) and the first term (9) are given, so you can write the iterative equation:
![a_n=(9)(\frac{2}{3})^{n-1}](https://tex.z-dn.net/?f=a_n%3D%289%29%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7Bn-1%7D)
And so the answer is C.
So.. both sides divided by 4.
Now u have 14/68=x/6 -5
Multiply all by 6
Now u have 84/68=x-30
21/17+510/17=x
531/17=x
X=31 4/17